Pengaruh Penempatan Kerja dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan PT X - Askary Hizburrahman, Hassan; Suherman, Suherman; Susita, Dewi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The Purpose of this research is to find out: 1) The effect of job placement on job satisfaction at PT X. 2) The effect of career deveplomet on job satisfaction at PT X. 3) The effect of job placement and career deveplomet on job satisfaction at PT X. The research method used was a survey method using a questionnaire with a quantitative approach. The sample used in this study was 83 employees who were determined by the slovin formula. The data analysis technique uses SPSS version 26 to process and analyze the data results. The results of this study reveal that there is a positive and significant effect of job placement on employee job satisfaction, there is a positive and significant effect of career development on employee job satisfaction, and there is a simultaneous positive and significant effect of job placement and career development on employee job satisfaction.